Gastroprotective effect of ethylacetate fraction of the leaves of Hannoa klaineana on aspirin and histamine-induced gastric ulcer in rats - Abubakar, Ibrahim; Muhammad Yankuzo, Hassan; Shuaibu Baraya, Yusha'u; Abubakar Gusau, Mu'azu (International Journal of Pharmacology and Toxicology, 2020)
Background: Peptic ulcer disease remains endemic in our society affecting about four million people every year worldwide. Hannoa klaineana is used traditionally in the treatment of various gastrointestinal diseases including ulcer.Aim: This study aims at evaluating the gastroprotective effect of ethylacetate fraction of the leaves of Hannoa klaineana (Simaroubaceae).Methods: The gastroprotective effect of ethylacetate fraction of the Hannoa klaineana (50, 100 and 200mg/kg b.wt) was evaluated using aspirin and histamine induced ulcer models.Results: In aspirin-induced ulcer model, the ethylacetate fraction of the Hannoa klaineana demonstrated significant (p<0.001) decreased in mean ulcer index with the maximum protective effect (99.84%) at 200 mg/kg against the gastric damages. While histamine-induced ulcer model, the solvent fraction significantly (p<0.001) decreased mean ulcer index with the protective effect up to 99.83% against the gastric lesions. In both models, a significant (p<0.001) increased in pH value coupled with significant (p<0.001) decreased in gastric volume, free and total acidity in rats pre-treated with varying doses of the ethylacetate fraction was found.Conclusion: The mechanism of gastroprotective effects of ethylacetate fraction of the Hannoa klaineana could be attributed to its ability to stimulate prostaglandins secretion or possess prostaglandins like-substances or suppression of histamine-induced vasospastic effect and gastric secretion.Â Â Â